Histoplasmosis masquerading as tuberculosis: A report of three cases in immunocompetent children - Anindita Mondal; Ram N Das; Uttara Chatterjee; Arijit Majumdar; Moumita Sengupta; Swagata Bhattacharyya; Ruchirendu Sarkar (Wolters Kluwer Medknow Publications, 2022)
The most common cause of granulomatous lymphadenitis in countries like ours is mycobactrium tuberculosis followed by atypical mycobacterial infection, fungal infections, parasitic infection, cat scratch disease, lymphogranuloma venereum (inguinal lymphadenopathy), and leprosy Here, we present three cases of lymphadenopathy due to histoplasmosis in immunocompetent children. Two of them presented with fever, lymphadenopathy, initially diagnosed as granulomatous lymphadenitis consistent with tuberculosis on FNAC and were put on antitubercular drugs. However, their condition gradually became worse. As the patients continued to deteriorate, subsequent lymph node biopsies were done and diagnosed as histoplasmosis. Third case presented with acute loss of vision with hepatosplenomegaly and lymphadenopathy. Initially considered as acute leukemia, but eventually established as histoplasmosis. Histoplasmosis should be considered as one of the possible causes of granulomatous lymphadenitis in children.